KOORDINASI GURU PAI DAN PENGAWAS DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PADA SMP DI PAPUA BARAT - Achmad Abubakar (EDUCANDUM, 2018)
This study aims to find out: the needs of SMPN for PAI teachers andsupervisors; level of quality of coaching and supervision towards the duties ofPAI Teachers; and the level of synergy between PAI teachers and supervisorsin improving the quality of learning. The study took samples from all PAI andSupervisor teachers in Sorong City and Sorong Regency. It was found thatthere were still 46% of education units in West Papua that had PAI teachers.Especially in junior high schools there are 23% of education units that do nothave PAI teachers (23% in SMPN and 25% in SMPS). As for supervisionneeds, Ministry of Religion West Papua provides 20% of supervisors of theamount needed. The level of quality of guidance on improving the quality ofduty of categorized PAI teachers is very high, the level of quality ability ofsupervisors to carry supervisory duties categorized is high, and the level ofsynergy PAI teachers and supervisors in improving the quality of learningcatetegorized is very high